Study of one-nucleon transfer reaction for the interaction of deutrons with the 9 Be nuclei within various theoretical models - Мендибаев, К; Уразбеков, Б; Лукьянов, С; Кутербеков, К; Джансейтов, Д; Исатаев, Т; Жолдыбаев, Т; Азнабаев, Д; Валиолда, Д; Кроха, В; Мразек, Д; Пенионжкевич, Ю; et al. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The angular distributions of protons, deuterons, tritons, and alpha particles emitted in the d+ 9 Be reaction at energies Elab(d) = 19.5 and 35.0 MeV were measured. The elastic scattering analysis is carried out in the framework of the optical model and the coupled channel method. The interaction potential of the d + 9 Be system was calculated using the double folding model using the three-body wave function α + α + n for the 9 Be nucleus. The analysis of the single-nucleon transfer reaction (d, p) and (d, t) in the framework of the coupled channel method is carried out. Spectroscopic amplitudes are calculated for various configurations of nuclear clusters.